Study To Assess Knowledge and Attitude of Hepatitis B Among Medical Students - Santosh D Patil; Ravindranath A Bhovi (Medsci Publications, 2016)
Background: HBV among health care professionalscan be prevented by strategies like vaccination, increasing awareness and following universal precautions. The present study was conducted on medical studentsto evaluate knowledge regarding Hepatitis BVirus and to know their vaccination status. Methodology: Cross sectional study was carried out onIst year MBBS students of BLDEU Shri B.M. Patil medical college Vijaypur.  All the students who were present on the day of data collection were included in the study and interviewed using pretestedquestionnaire. Data was analyzed using percentages. Results-Most of the students had good knowledge about disease, causative agent and modes of transmission & prevention. Astonigshly half of them were unaware of high risk of transmission to health professional. Conclusion -It is recommended for Hepatitis B vaccination for all unimmunized students who enter medical profession. The orientation and sensitization programme should be held to create awareness regarding HBV infection.